1994
DOI: 10.1089/neu.1994.11.613
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Fluid Percussion Device

Abstract: This report examines a modified fluid percussion device with specific improvements made to address deficiencies found in previously reported devices. These improvements include the use of a cylindrical saline reservoir made of stainless steel, placement of the reservoir in a 15-degree head-up position for the easy release of air bubbles, placement of the fluid flushing outlet and the pressure transducer close to the piston on the same plane, with both perpendicular to the direction of the piston, and adjustabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The lateral fluid percussion model of experimental brain trauma of moderate severity (2.3 6 0.1 atm) was performed using equipment based on similar well-recognised and characterised systems (Dixon et al, 1987;McIntosh et al, 1989;Yamaki et al, 1994). Our model consists of a horizontally mounted 10ml syringe connected via a luer-loc and three-way connection to two identical lengths of plastic tubing, one connected to a pressure transducer and the other to the craniotomy site.…”
Section: Methodsmentioning
confidence: 99%
“…The lateral fluid percussion model of experimental brain trauma of moderate severity (2.3 6 0.1 atm) was performed using equipment based on similar well-recognised and characterised systems (Dixon et al, 1987;McIntosh et al, 1989;Yamaki et al, 1994). Our model consists of a horizontally mounted 10ml syringe connected via a luer-loc and three-way connection to two identical lengths of plastic tubing, one connected to a pressure transducer and the other to the craniotomy site.…”
Section: Methodsmentioning
confidence: 99%
“…The main advantages of the fluid percussion model are similar to that described for the CCI model in that it induces graded levels of brain injury and produces axonal injuries and contusions, as well as impaired neurologic motor function and cognitive deficits (Dixon et al, 1987;McIntosh et al, 1987;Yaghmai and Povlishock, 1992). It has also been modified and widely applied (Sullivan et al, 1976;Povlishock et al, 1983;Dixon et al, 1987;McIntosh et al, 1989;Yamaki et al, (1994) to other animal species including the rat, dog, rabbit, cat and swine and has been used in combination with microdialysis in the rat Busto et al, 1987;Kawamata et al, 1995;Katayama et al, 1990). Also, fluid flow characteristics (i.e.…”
Section: Fluid Percussion Injurymentioning
confidence: 99%
“…Recently, reports have shown that midline fluid percussion (MFP) injury in a rat model produced DAI in contrast to the lateral fluid percussion injury rat model (Yamaki et al 1994;Iwamoto et al 1997). Therefore, we used the surgical procedure for MFP injury in the rat model.…”
Section: Surgical Proceduresmentioning
confidence: 99%